PERTIMBANGAN HAKIM DALAM MENILAI SAKSI MAHKOTA PADA TINDAK PIDANA MEMBANTU MELAKUKAN PEMBUNUHAN BERENCANA - Icha Hanifah Razzak; Putri Maha Dewi (Sebelas Maret University, 2023)
This study aims to determine whether the crown witness was considered by the judge in proving the crime of assisting premeditated murder in Decision Number 41/Pid.B/2021/PN Bil. This research is a normative legal research that is prescriptive and applied. This research uses a case approach. The legal materials used are primary legal materials and secondary legal materials. The legal material collection technique used in this legal research is literature study. The results of this study indicate that in Decision Number 41/Pid.B/2021/PN Bil, the crown witness was considered by the judge. The use of crown witnesses is allowed while still observing the provisions in submitting crown witnesses. These provisions are the separation of case files, lack of evidence, and criminal acts in the form of participation. The judge's consideration in Decision Number 41/Pid.B/2021/PN Bil which uses a crown witness is in accordance with the provisions of the Criminal Procedure Code. Based on the evidence submitted by the public prosecutor which was strengthened by the testimony of the crown witness, the judge was convinced that the criminal act had actually occurred and the defendant was the one guilty of committing it. The use of crown witnesses in this case was able to facilitate the judge in imposing punishment on the defendant who helped commit premeditated murder.Keywords: Crown Witness; Evidence; Judge's Consideration